MaqÄá¹£id SharÄ«'ah Flexibility to Overcome COVID-19 in Indonesia: From Government Policies to FatwÄ of Council of Indonesian Ulema (MUI), Nahdlatul Ulama (NU), and Muhammadiyah - Mashuri, Mashuri; Nur, Iffatin; Muttaqin, Muhammad Ngizzul (Fakultas Syariah, 2021)
Abstract: Since its first appearance in Wuhan, China, the COVID-19 has become a worldwide concern, and now its impact as a pandemic has been felt globally. The number of cases, the death tolls, the steps that each countryâ€™s government must take, and the activities of social life that must be practiced by all people, among others, are interesting phenomena to study. This paper tries to examine from the Islamic perspective, regulations issued by the Indonesian Government and edicts issued by religious institutions and organizations in Indonesia, especially of the Indonesian Council of Ulema (MUI), Nahdlatul Ulama (NU), and Muhammadiyah, in response to the COVID-19 outbreak in Indonesia. This study is qualitative research with a discourse analysis that discusses the legal-socio-contextual aspects of the rules and fatwÄs/edicts with the maqÄá¹£id sharÄ«'ah (purposefulness of Islamic law) approach. The results show that the regulations and edicts are in accordance with fundamental values in the discourse of obtaining the objectives of Islamic law (maqÄá¹£id sharÄ«â€™ah), and the necessity to preserve oneâ€™s soul is prioritized over preserving oneâ€™s religion since practicing religious teachings can only be conducted whenever oneâ€™s soul is preserved.Keywords: Pandemic; COVID-19; FatwÄ; Indonesian Regulation; MaqÄá¹£id SharÄ«'ah.Â Abstrak: Sejak pertama kali muncul di Wuhan, China, COVID-19 telah menjadi perhatian dunia dan kini dampaknya sebagai pandemi sudah terasa secara global. Banyaknya kasus, jumlah korban meninggal, langkah-langkah yang harus diambil oleh pemerintah masing-masing negara, dan aktivitas kehidupan sosial yang harus dilakukan oleh semua orang menjadi fenomena yang menarik untuk dikaji. Tulisan ini mencoba mengkaji, dari perspektif Islam, peraturan yang dikeluarkan oleh Pemerintah Indonesia dan fatwa yang dikeluarkan oleh lembaga dan organisasi keagamaan di Indonesia, khususnya Majelis Ulama Indonesia (MUI), Nahdlatul Ulama (NU), dan Muhammadiyah, dalam menyikapi mewabahnya COVID-19 di Indonesia. Penelitian ini merupakan penelitian kualitatif dengan analisis wacana yang membahas aspek legal-sosio-kontekstual terhadap aturan dan fatwa dengan pendekatan maqÄá¹£id syari'ah (tujuan hukum Islam). Hasil penelitian menunjukkan bahwa peraturan dan fatwa tersebut sesuai dengan nilai-nilai fundamental dalam wacana pencapaian tujuan hukum Islam (maqÄá¹£id syari'ah) dan keharusan memelihara jiwa lebih diutamakan daripada memelihara agama karena mengamalkan ajaran agama hanya dapat dilakukan manakala jiwa seseorang terpelihara.Kata Kunci: Pandemi; COVID-19; Fatwa; Peraturan Indonesia; MaqÄá¹£id SharÄ«'ah.